Simultaneous free and bound radioactive vitamin B(12) urinary excretion test - Bell, T. K. (1965)
The absorption of vitamin B(12) following the simultaneous administration of (58)Co B(12) and a complex of (57)Co B(12) with human gastric juice was assessed by measurement of urinary excretion of radioactivity. Sixteen control subjects, 13 patients with pernicious anaemia, and four who had had total gastrectomy were studied. The method proved a reliable means of detecting those with intrinsic factor deficiency.